Experimental design of switchable solvent-based liquid phase microextraction for the accurate determination of etrimfos from water and food samples at trace levels by GC-MS - Firat, Merve; Chormey, Dotse Selali; Bakirdere, Sezgin; Turak, Fatma (SPRINGER, 2019)
Presented in this study is a simple but efficient switchable polarity solvent microextraction strategy for etrimfos preconcentration from water and food samples for quantification by gas chromatography mass spectrometry. Repeatability of the extraction process and instrumental measurements were enhanced by using deuterated bisphenol A as internal standard. Significant parameters of the extraction method were fitted into an experimental design model to study the effects of parameters on extraction output, as well as mutual effects of combined parameters. The design model was formed with 51 experimented data obtained from the combination of sodium hydroxide volume, switchable solvent volume, and vortex period at three levels. The method was validated by applying optimum conditions attained from the model predictor. The detection limit was found to be 1.3 ng/mL and it corresponded to an enhancement factor of about 54 folds when compared to direct GC-MS measurement. Etrimfos was not detected in the water and food samples tested but the results (92-107%) obtained from spiked recovery experiments established that etrimfos when present in the selected matrices can be accurately and precisely quantified.
Keywords: Etrimfos; Switchable solvent; GC-MS; QuEChERS; Experimental design; OCCUPATIONAL-EXPOSURE; PESTICIDE-RESIDUES; EXTRACTION; RISK; Environmental Sciences & Ecology